Junk food use and neurodevelopmental and growth outcomes in infants in low-resource settings - Chiwila, Melody K.; Krebs, Nancy F.; Manasyan, Albert; Chomba, Elwyn; Mwenechanya, Musaku; Mazariegos, Manolo; Sami, Neelofar; Pasha, Omrana; Tshefu, Antoinette; Lokangaka, Adrien; Goldenberg, Robert L.; Bose, Carl L.; et al. (Frontiers in Public Health, 2024)
Introduction Feeding infants a sub-optimal diet deprives them of critical nutrients for their physical and cognitive development. The objective of this study is to describe the intake of foods of low nutritional value (junk foods) and identify the association with growth and developmental outcomes in infants up to 18 months in low-resource settings. Methods This is a secondary analysis of data from an iron-rich complementary foods (meat versus fortified cereal) randomized clinical trial on nutrition conducted in low-resource settings in four low- and middle-income countries (Democratic Republic of the Congo, Guatemala, Pakistan, and Zambia). Mothers in both study arms received nutritional messages on the importance of exclusive breastfeeding up to 6 months with continued breastfeeding up to at least 12 months. This study was designed to identify the socio-demographic predictors of feeding infants’ complementary foods of low nutritional value (junk foods) and to assess the associations between prevalence of junk food use with neurodevelopment (assessed with the Bayley Scales of Infant Development II) and growth at 18 months. Results 1,231 infants were enrolled, and 1,062 (86%) completed the study. Junk food feeding was more common in Guatemala, Pakistan, and Zambia than in the Democratic Republic of Congo. 7% of the infants were fed junk foods at 6 months which increased to 70% at 12 months. Non-exclusive breastfeeding at 6 months, higher maternal body mass index, more years of maternal and paternal education, and higher socioeconomic status were associated with feeding junk food. Prevalence of junk foods use was not associated with adverse neurodevelopmental or growth outcomes. Conclusion The frequency of consumption of junk food was high in these low-resource settings but was not associated with adverse neurodevelopment or growth over the study period.